Analisa Strategi Komunikasi Politik Anggota DPR Aceh Terpilih Periode 2024-2029 pada Partai Lokal Aceh - Retno Wulandari; Edison Bonartua Hutapea (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The phenomenon of the local Aceh party's victory in the 2024 legislative election demonstrates the success of political communication strategies employed by the elected members of the Aceh Regional House of Representatives. This study aims to analyze the political communication strategies used by local party members in winning the election and how these strategies build closeness with voters in Aceh. The research method is qualitative with a case study approach, involving in-depth interviews, observations, and document analysis related to political campaigns. The results indicate that a combination of interpersonal communication, utilization of social media, and integration of local cultural values are key to the success of the local party’s political communication strategy. This study contributes new insights by highlighting the importance of local wisdom-based political communication and the role of traditional and religious leaders in strengthening political support in a special autonomous region like Aceh. The findings can serve as a reference for developing more effective and contextual political communication strategies in regions with similar characteristics.